PENGGUNAAN TEKNIK MIND MAPPING DALAM PEMBELAJARAN BAHASA INGGRIS UNTUK MENINGKATKAN KEMAMPUAN MENULIS SISWA KELAS XI - Sapura, Azie Ony; Ramdhani, Ahmad; Achmad, Abdul Kholid (Universitas Muhammadiyah Gresik, 2024)
Using the mind map technique to improve English writing skills in class XI Saintek 1 SMA Muhammadiyah 1 Gresik students. This method is a visual approach that allows students to organize and connect their ideas in a hierarchical picture. This research aims to explore the effectiveness of mind mapping techniques in improving students' writing skills. This research method uses classroom action research methods. The research results showed that there was a significant increase in students' writing skills after using the mind map technique. These findings can support the use of techniques as an effective strategy in improving the English writing skills of class XI Saintek 1 SMA Muhammadiyah 1 Gresik students. This research shows that 31% are able to write in English, and there is an increase of 83% in learning English using the mind map technique.